Cyborg as a Destroyer of G. Agamben’s Anthropological Machine - Dementavičienė, Augustė; Dranseika, Donatas (Baltic Journal of Political Science, 2020)
The ambition of this paper is to reason the consistency and logical coherence of the concept of Giorgio Agamben‘s anthropological machine. The important puzzle is that although Agamben emphasized the importance of having this machine destroyed, he did not suggest any clear and specific way to achieve it. The concept of a cyborg, developed by Donna Haraway, has been introduced to rethink the anthropological machine through the eyes of the cyborg. So, the main question of this paper is: whether or not the destruction of the anthropological machine is possible using the concept of the cyborg? The cyborg has been chosen because it blurs the boundaries among various oppositions. Oppositions (e.g. animal / human, man / woman, public / private) are exactly what the anthropological machine establishes, moreover, it also empowers itself through the existence of those oppositions. Cyborg has material substance inside its own “body” right from the beginning, so through this understanding we can incorporate the questions about the environment (broadly understood) and the self in every cyborg. The cyborgs, paraphrasing Haraway, are very good at cat’s cradle game when the interactions could be seen very clearly between our everyday acts and some global or political issues.